Prevalencia de intoxicaciones por órganofosforado asociado a intento autolítico en usuarios as atendidos en el Hospital Regional Isidro Ayora de Loja durante el periodo 2009 2013 - Gómez Villegas, Charlie Daniel (2015)
A large number of organophosphate insecticides are used in the everyday world, for that reason this poisoning is a major health problem at the provincial level. This research is based on a study of retrorospectivo and transverse kind in the area of Isidro Ayora Hospital of Loja during the period 1 January 2009 to 31 December 2013. The universe are patients diagnosed with poisoning in general during the mentioned period of time and only shows organ phosphorous-poisoned patients associated with attempted suicide. In this study what was possible to obtain: prevalence, gender, age frequent, frequent times of year and mortality; by reviewing medical records and books of that hospital discharge. As a preventive study to improve the rates of morbidity and mortality in this health issue. In the results there were 63 patients poisoned by phosphorous organ to commit suicide, of which 31 belong to the male and 32 female, the year of highest incidence was in 2013 with 18 cases and a prevalence of 15.64 per 10,000 inhabitants, plus the Frequently ages in the study were age 12 to 22 years, existing death of 1 patient with a low mortality rate of 1.59%.